Investigation of growth and survival of some pathogens in koumiss - Mustafa Atasever; Fatih Ramazan İstanbullugil (MANAS: Journal of Engineering)
The aim of this study was to investigate the growth and survival of Escherichia coli O157:H7, Listeria monocytogenes and Staphylococcus aureus in koumiss produced from raw mare's milk during the fermentation process. E. coli O157:H7 (Group 1), L. monocytogenes (Group 2) and S. aureus (Group 3) were added to the raw mare’s milk that would used to producing koumiss and a combination of all three pathogens (Group 4) was inoculated. These microorganisms were introduced at 106 CFU/mL concentration into the raw mare’s milk, which served as the base for koumiss production. During fermentation, microbiological and chemical analyses were carried out by taking one sample from each group at the 1st, 5th and 24th hours and at the 2nd, 3rd, 4th and 5th days. As a result of analyzes; pH, dry matter, and protein content declined, while titration acidity and alcohol content increased. A positive correlation was found between the bacterial count and the utilized pathogenic microorganisms. Conversely, a negative correlation was observed with the count of yeast molds. Remarkably, the counts of E. coli O157:H7, L. monocytogenes, and S. aureus reduced starting from the fifth hour of fermentation and diminished to undetectable levels by the second day. This decline in pathogenic microorganisms below detectable thresholds during the fermentation process was linked to the rise in titration acidity and alcohol content and the decrease in pH.